Stapling of an endobronchial suction tube with the bronchus during robot-assisted right lower lobectomy: a case report - Hiroto Tanaka; Teruhiro Aoki; Makoto Oda; Yoshimasa Inoue (Surgical Case Reports)
Abstract Background Troubleshooting intraoperative complications requires careful management, and the safest technique should be chosen. We recently experienced a unique intraoperative bronchial complication during pulmonary lobectomy in robot-assisted thoracic surgery (RATS). There is no consensus on whether to continue RATS or convert to a more familiar technique, such as video-assisted thoracic surgery (VATS) or thoracotomy, for intraoperative complications that occur during RATS, and the decision should be determined individually. Case presentation A 74-year-old woman with primary lung adenocarcinoma (clinical stage IA2) underwent robot-assisted right lower lobectomy under one-lung ventilation and CO2 insufflation. Intraoperatively, the anesthesiologist placed the endobronchial suction tube in the right bronchus with intention of maintaining the right lung collapse, which was simultaneously stapled with the right lower bronchus during the right lower lobe bronchial closure using a robotic stapler. During robot-assisted manipulation, we removed the staples involved with the suction tube, one by one, using robotic-arm forceps and sutured the partially opened stump. Subsequently, the bronchial stump was covered with a pedicled pericardial fat pad. The postoperative course was uneventful, and the patient developed no complications when followed up 8 months after discharge. Hence, we could rectify this intraoperative bronchial complication using a robot-assisted technique and avoid conversion to VATS or thoracotomy. Conclusion The precise manipulation techniques in RATS contributed to facilitate the successful execution of surgical procedures, such as staple removal and re-suturing of the bronchial stump and may be a useful as a method for such troubleshooting such intraoperative complications.